Reverse modeling of car door using laser scanning methodology - Nur Fasehah, Maarop (2010)
Reverse engineering was not commonly knew by other people and mainly employed for shape design applications. By use of this method, under developed countries can decreasing the technologic gap between itself and industrial countries. 3D scanner is one of the tools in the reverse engineering. The recent advancement of 3D non-contact laser scanners enables fast measurement of parts by generating a huge amount of coordinate data for a large surface area in a short time. Although the scanning process itself is not new, the processing power requirements of the captured cloud data is enormous, and only now, with the development and affordability of high powered computers, can the software be used effectively and efficiently. Complied with the demanding of the environment in the industry, each company will arrange the strategy in increase their quality. One of the alternatives that can be developing to improve the quality is research in the curvature surface. So, the objectives of the project are to scan and gather 3D point’s clouds of car door and to generate and analyze the quality of car door 3D model. Firstly the door panel needs to be uninstalling from the car body to make the scanning process become easier. Then the surface of the door is altered because the scanner is using reflection concept. A density of a material can be determined by the reflection also act as the medium to get the true image for an object. Lastly, start scanning and then edit the scanned product using Polywork software as a way to condition the result obtained. Thus a lot of quality improvement can be developing in any sector by using the data of the 3D model such as important in study of safety